(untitled) (Tạp chí Y học Cộng đồng, 2024)
Objective: To assess the knowledge of the population in Thuan An City, Binh Duong Province, regarding hypertension according to Traditional Medicine combined with Modern Medicine. Subjects and research methods: A cross-sectional descriptive study was conducted to survey the knowledge of 384 residents aged 18 and older living in Thuan An City, Binh Duong Province, who agreed to participate in the study. Results: 82.1% of the total participants had a knowledge level of average or higher about hypertension according to Traditional Medicine combined with Modern Medicine, with 24% having a good knowledge level. Analysis of correlations identified several factors associated with the population’s knowledge of hypertension according to Traditional Medicine combined with Modern Medicine, including occupation and income. Specifically, the group engaged in intellectual labor had 2.52 times lower odds of having poor knowledge compared to other occupations (students, unemployed, retirees, etc.), and those with an average monthly income above 10 million VND had 2.66 times lower odds of having poor knowledge compared to those with a monthly income below 5 million VND. Conclusion: The knowledge of the population in Thuan An City, Binh Duong Province, about hypertension according to Traditional Medicine combined with Modern Medicine is at an average level.